MAPPING AND CRITICAL LAND MANAGEMENT AS EFFORTS TO CONTROL CLIMATE CHANGE IN LAMONGAN - Isa Ma'rufi; Eri Witcahyo (UNEJ e-Proceeding, 2012)
Development of agricultural sector should be able to develop the potential ofnatural resources, particularly optimization of land and environmentally sounding. Inaddition to the program intensification, extensification and agriculture diversification,rehabilitation of land is also an effort that can be taken to scale up the productivity of land.The purpose of study was to analyze the potential and critical level of land which ispresented in the form of maps and recommended management actions as efforts to controlclimate change in Lamongan. Sample of this study was two groups; there are soilcomponents and communities. Soil components which studied were physical environment,morphology and chemical of land, topography, land closures and nature of erosion.Communities variable which studied were perceptions of soil fertility, plant speciescommonly planted, plan habit at certain seasons, agricultural issues that commonly arise orencountered, strategies and expectations of development of the land. Laboratory results ofsoil texture in six districts showed that the majority districts were having clay loam, claydust, and dusty clay loam textured. From the results of the laboratory, soil textures at thedistricts are less than ideal for agriculture but still potential. The average of land potentiallevel at six districts was adequate, although there are some areas and villages were stillmoderate moreover very critical. Each district showed their average land potential, thereare moderate at Sukorame District, Bluluk District, Modo District, Ngimbang District andSambeng District, while Mantup District has the potential land. It is recommended for themanagement of critical land of rice fields in six districts was studied by conservationfarming which combine mechanical and vegetative conservation techniques in anintegrated farming patterns. The goals are to increase farm productivities and farmerincomes, reducing the rate of erosion, and increase farmer participation in conservation ofsoil and water resources.